PENGARUH AUDIT TENURE, ROTASI KAP, UKURAN KAP, DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP KUALITAS AUDIT - Aris Tri Wicaksono; Agus Purwanto (Diponegoro Journal of Accounting, 2021)
The purpose of this study is to examine the effect of audit tenure, public accounting firms rotation, public accounting firms size, and auditor industry specialization on audit quality. Proxy measurements for audit quality is using discretionary accrual Modified Jones model, while audit tenure is measured by calculating the years in which the same auditor has collaborated with clients. Accounting firms rotation, accounting firms size, and auditor industry specialization is measured by using dummy variables. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019. Sampling was done by using purposive sampling method. The total sample in this study was 403. The multiple linear regression was used to analyze data. The results showed that audit tenure negatively affecting on audit quality, accounting firms rotation positively affecting on audit quality, and auditor industry specialization positively affecting on audit quality while the public accounting firms size has no effect on audit quality.